Timed pregnancy in rats: a simple and reliable approach in determining the stage of oestrous for non-histologists - Aminuddin, Niferiti; Abdul Razak, Tariq; Mohd Rashid, Muhammad Hakimi; Mohd Noor, Noriah (2015)
There are a few approaches that enable us to time the pregnancy. Recent techniques had shown that observation of unstained smear is more practical than stained smear. However, with simple modifications, methylene blue dye staining technique can be a practical and reliable approach for non-histologists. 10 healthy fertile male and 30 female Sprague Dawley rats age 10 weeks old were acclimatized. At 12 weeks old, the oestrous cycle of the female rats were determined. Two to three drops of normal saline ( NaCl 0.90%) was flushed into the vagina for three times. One to two drops of the cells suspension was placed on the slide .The slide was dried with a hot plate. The cells suspension was treated with 0.1% methylene blue dye for 20 to 30 seconds. The surplus was removed from the slide by dipping in a container filled with slowly running tap water for three times. The slide can be immediately examined under the light microscope at 40x and 100x magnification. The four oestrous cycle stages namely proestrous, estrous, metestrous and diestrous were clearly identified with the methylene blue dye staining method. All 30 female rats were successfully impregnated. The methylene blue dye treatment can be done within 20-30 seconds, as compared to 45 minutes in previous study. The smear can be accurately observed by the beginners directly under the light microscope without the aid of histologists. The methylene blue dye stained smear is easy to interpret as the characteristics of the cells are well discernible, relatively inexpensive and doesn’t requires complex preparation.